The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/asjc.2472
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy control system design for wheel slip prevention and tracking of desired speed profile in electric trains

Abstract: This study proposes an anti-slip control system for electric trains based on the fuzzy logic theory, which prevents the wheels from slipping during the acceleration and simultaneously tracks the desired speed profile. To improve the control performance, the train longitudinal velocity and the slip ratio are estimated. By using a Field Oriented Control (FOC), the angular speed of the traction motor is controlled. The fuzzy control system determines the desired angular speed of the traction motor as the referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…Here, the two systems are briefly analyzed first. Fuzzy control [8,9] includes access terminals, monitoring equipment, access and output ports, mechanisms, controlled objects, and inspection systems. The basic principle of fuzzy control is shown in Figure 4.…”
Section: Application Of Ai In Electrical Automationmentioning
confidence: 99%
“…Here, the two systems are briefly analyzed first. Fuzzy control [8,9] includes access terminals, monitoring equipment, access and output ports, mechanisms, controlled objects, and inspection systems. The basic principle of fuzzy control is shown in Figure 4.…”
Section: Application Of Ai In Electrical Automationmentioning
confidence: 99%
“…As shown in Figure 5, to match the load with the solar array, in order to absorb the maximum power, the buck converter is used as a power processor [10]. [12]- [13]. To design a fuzzy controller and to select fuzzy rules, there should be a complete understanding of the photovoltaic system's behavior.…”
Section: Dc-dc Buck Convertermentioning
confidence: 99%
“…In this study, the dehydration of a PEMFC was analysed through classification based on the knowledge from an operator over a FC. Results revealed that suitable nonlinearities like electrical features and uncertainties can be mirrored with linguistic rules, an essential feature of this tool [19]. However, one of the main disadvantages of fuzzy logic strategies is the computational requirement when features are increased and thus, rules are expanded [20].…”
Section: Introductionmentioning
confidence: 99%